Synthesis and Performance Optimization of a Switching Nano-crossbar Computer - Alexandrescu, Dan; Altun, Mustafa; Anghel, Lorena; Bernasconi, Anna; Ciriani, Valentina; Frontini, Luca; Tahoori, Mehdi (IEEE, 2016)
Beyond CMOS, new technologies are emerging to extend electronic systems with features unavailable to siliconbased devices. Emerging technologies provide new logic and interconnection structures for computation, storage and communication that may require new design paradigms, and therefore trigger the development of a new generation of design automation tools. In the last decade, several emerging technologies have been proposed and the time has come for studying new adhoc techniques and tools for logic synthesis, physical design and testing. The main goal of this project is developing a complete synthesis and optimization methodology for switching nano-crossbar arrays that leads to the design and construction of an emerging nanocomputer. New models for diode, FET, and four-terminal switch based nanoarrays are developed. The proposed methodology implements both arithmetic and memory elements, necessitated by achieving a computer, by considering performance parameters such as area, delay, power dissipation, and reliability. With combination of arithmetic and memory elements a synchronous state machine (SSM), representation of a computer, is realized. The proposed methodology targets variety of emerging technologies including nanowire/nanotube crossbar arrays, magnetic switch-based structures, and crossbar memories. The results of this project will be a foundation of nano-crossbar based circuit design techniques and greatly contribute to the construction of emerging computers beyond CMOS. The topic of this project can be considered under the research area of “Emerging Computing Models” or “Computational Nanoelectronics”, more specifically the design, modeling, and simulation of new nanoscale switches beyond CMOS.
Keywords: Performance optimization; Switching nanocrossbar computer